Evaluasi Penerapan Manajemen Waktu Pada Proyek Pembangunan Ciputra School of Business Makassar - Bona Eirene Mangape; Josefine E Latupeirissa; Lintje Tammu Tangdialla (Paulus Civil Engineering Journal, 2021)
The construction world there are still many projects whose implementation does not match the specified time. Therefore, it is necessary to evaluate the application of time management in the construction project of the Ciputra School of Business building which experienced delays in several sub-sections of work. The research method used in this research is descriptive analysis method. From the results of the study, it can be seen that in the implementation of the S-curve project it is used as a time schedule in monitoring progress and scheduling work, contractors need to do work in parallel with the fast tracking acceleration method and apply overtime so that weekly and monthly targets are met. From the results of the analysis, it can be concluded that the control uses the S-curve where the baseline is carried out every three months for 1 year during the implementation period.